New photocell timing gates for measuring the maximum velocity of futsal players - Apriantono, T.; Herman, I.; Adiprawita, W.; Winata, B. (Sport Sciences for Health, 2022)
Introduction A fully automatic timing system is expensive and is normally used by recognized athletes or in international competitions. This study aims to develop a new photocell timing gate at an affordable price with a high maximum velocity (Vmax) for junior futsal players. Furthermore, it aims to compare new and validated photocell timing (NPT) gates with validated timing (VT) and manual hand-held timing (MHH).